Mature and immature teratoma: A report from the second Italian pediatric study. Issue 7 (28th January 2015) - Terenziani, Monica; D'Angelo, Paolo; Inserra, Alessandro; Boldrini, Renata; Bisogno, Gianni; Babbo, Gian Luca; Conte, Massimo; Dall' Igna, Patrizia; De Pasquale, Maria Debora; Indolfi, Paolo; Piva, Luigi; Riccipetitoni, Giovanna; et al.
<x xml:space="preserve">Abstract</x> Background Teratomas demonstrate a benign clinical behavior, however they may recur with malignant components or as teratoma, and in a small group of patients prognosis could be fatal. After the first Italian study, we collected cases of teratoma, alongside the protocol for malignant germ cell tumors. Procedure Patients with teratoma were collected from 2004 to 2014. Teratomas were classified according to the WHO classifications, as mature and immature. Patients with pathological aFP and/or bHCG, and those with a malignant germ cell component were not included. Results The study enrolled 219 patients (150 mature, 69 immature teratomas) with a median age at diagnosis of 42 months. The primary sites involved were: 118 gonadal and 101 extragonadal teratomas. Two females with ovarian teratoma had a positive family history. Complete and incomplete surgeries were performed in 85% and 9% of cases. Seventeen events occurred: six females had a second metachronous tumor (5 contralateral ovarian teratoma, 1 adrenal neuroblastoma) and 11 teratomas relapsed/progressed (3 mature, 8 immature teratomas). Two patients died, one of progressive immature teratoma and one of surgical complications. At a median follow up of 68 months, the event‐free, relapse‐free, and overall survival rates were 90.6%, 94.3%, 98.6%, respectively. Conclusions Teratomas show a good prognosis, especially the mature ones: surgery and follow‐up remain the standard approach. Incomplete surgery in immature teratoma is the group at greatest risk of relapse. Bilateral ovarian tumors are a possibility, and the rare family predisposition to ovarian mature teratoma warrants further analyses. Pediatr Blood Cancer 2015;62:1202–1208. © 2015 Wiley Periodicals, Inc.